2015
DOI: 10.1155/2015/801308
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Multiattribute Decision Making Model for Evaluating Students’ Satisfaction towards Hostels

Abstract: This paper proposes a new hybrid multiattribute decision making (MADM) model which deals with the interactions that usually exist between hostel attributes in the process of measuring the students' satisfaction towards a set of hostels and identifying the optimal strategies for enhancing their satisfaction. The model uses systematic random stratified sampling approach for data collection purpose as students dwelling in hostels are "naturally" clustered by block and gender, factor analysis for extracting large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Hostel users face a lot of storage problems due to limited space in the wardrobe; they cannot store their clothes, shoes, and other storage accessories [19]. The prior study indicated that some students were not satisfied due to the availability of CCTV cameras in their residences and the effectiveness of security guards [8]. [4] concluded that staff was the most important dimension in explaining the willingness to recommend hostels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hostel users face a lot of storage problems due to limited space in the wardrobe; they cannot store their clothes, shoes, and other storage accessories [19]. The prior study indicated that some students were not satisfied due to the availability of CCTV cameras in their residences and the effectiveness of security guards [8]. [4] concluded that staff was the most important dimension in explaining the willingness to recommend hostels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khatri designed and assessed the solar PV Plant in the girls' hostel at MNIT University, India. (Krishnan et al, 2015) used a hybrid MCDM technique to determine the satisfaction of the hostel students. The weights of the criteria were determined through Mikhailov's fuzzy analytical hierarchy process (MFAHP).…”
Section: Related Workmentioning
confidence: 99%
“…Internal ambiance aspects such as good lighting, air-conditioning, and spatial layout of a restaurant could help in creating a better dining experience for customers to repurchase (Harris & Goode, 2010). Overall safety factor of a restaurant can be assessed from whether the restaurant has basic features such as CCTVs, smoke detectors, fire extinguisher, and emergency exits (Krishnan et al, 2014). External appearance is the first observation that the clients will experience even before getting restaurant (Rande, 1995); Worn-off paint or burnt-out lights may create a poor impression of the restaurant.…”
Section: Table 1 Continuedmentioning
confidence: 99%